2011
DOI: 10.1007/s10704-011-9653-3
|View full text |Cite
|
Sign up to set email alerts
|

General size effect on strength of bimaterial quasibrittle structures

Abstract: This paper presents a general size effect equation for the strength of hybrid structures, which are made of two dissimilar quasibrittle materials with a thin and weak bimaterial interface. Depending on the material mismatch and structure geometry, a singular stress field could occur at the bimaterial corner. For structures with strong stress singularities, an energetic size effect is derived based on the equivalent linear elastic fracture mechanics and asymptotic matching. For structures without stress singula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…::Þ ð1Þ where k is the generalized stress intensity factor of a notch of bi-materials and F is the applied load, k c the critical generalized stress intensity factor or fracture toughness for a specific notch, which is a function of the notch angle b, tensile and shear strengths r c ; s c , mode I fracture toughness G Ic , and mode-mixity u and other parameters. Recently, Le [15] found that a size effect exists for the strong stress singularity at concave bi-material notches like the ones used in the current investigation. The strong stress singularity was calculated in our previous work [31].…”
Section: Introductionmentioning
confidence: 75%
“…::Þ ð1Þ where k is the generalized stress intensity factor of a notch of bi-materials and F is the applied load, k c the critical generalized stress intensity factor or fracture toughness for a specific notch, which is a function of the notch angle b, tensile and shear strengths r c ; s c , mode I fracture toughness G Ic , and mode-mixity u and other parameters. Recently, Le [15] found that a size effect exists for the strong stress singularity at concave bi-material notches like the ones used in the current investigation. The strong stress singularity was calculated in our previous work [31].…”
Section: Introductionmentioning
confidence: 75%
“…(1) the peak load is reached when the stress intensity factor reaches a critical value (Carpinteri 1987;Dunn et al 1996;Gomez and Elices 2003), (2) the peak load is attained when the stress at a certain distance c f from the notch tip reaches the material tensile strength (Ritchie et al 1973;Ba zant and Yu 2006), and (3) the peak load is realized when the energy release rate of an equivalent crack that represents the FPZ reaches a critical value, i.e., the fracture energy (Le et al 2010;Le 2011). These criteria are all cast in the framework of linear elastic fracture mechanics, which can be used to derive the large-size asymptote of the size effect.…”
Section: Case Of Strong Stress Singularitymentioning
confidence: 99%
“…For Mode-I loading, all three criteria essentially yield the same form of the power-law size effect. Among these criteria, the second criterion is relatively straightforward to use, because the first criterion adopts a geometrydependent critical stress intensity factor, which needs to be measured for every notch angle (Ba zant and Yu 2006), and the third criterion requires determination of the energy release at the tip of an equivalent crack through the solution of an ancillary boundary value problem (Leguillon 2002;Le et al 2010;Le 2011).…”
Section: Case Of Strong Stress Singularitymentioning
confidence: 99%
“…where £ = effective modulus of composites or steel, = geometry-dependent constant which can be determined by solving an auxiliary small-scale cracking problem [2,3,8,13,14]; Gf = fracture energy and Cf = length of the fully developed FPZ. Evidently, without knowing c/, the fracture energy Gf cannot be identified by fitting size effect data with Eq.…”
Section: Fig 4 Curves Of Load Versus Relative Displacement (Measuredmentioning
confidence: 99%
“…As such, the energetic argument of linear elastic fracture mechanics (LEFM) cannot directly be used to characterize the crack initiation from the comer. Rather, one must take into account the development of a finite fracture process zone (FPZ) at the inner comer, which can be quite large when dealing with a quasi-brittle material such as fiber composite [2,3]. For a propagating crack, the size of the FPZ is approximately constant, a material characteristic.…”
mentioning
confidence: 99%